EKSTRAKSI DAN IDENTIFIKASI OLEORESIN ASAM GELUGUR (Garcinia atroviridis Griff ex T. Anders) (Extraction and Identification of Gelugur Oleoresine (Garcinia atroviridis Griff ex T. Anders) - Hutajulu, Tiurlan Farida; Hartanto, Eddy Sapto (Baristand Industri Banda Aceh, 2014)
Extraction and Identification on oleoresin of Gelugur Acid has beenconducted, identifying research oleoresin of Gelugur Acid (Garcinia atroviridis Griff ex T.Anders) aims to find out how to extract oleoresin by using alcohol solvents with differentvariations of the extraction using alcohol 30%, 70% and 95%. Oleoresin extractionresults obtained information that the higher the concentration of alcohol will resulted in ahigher oleoresin obtained. At these identification was also obtained information about thecontent of organic acids such as ascorbic acid at 51 mg / kg; tartart acid 35 mg / kg; malicacid 28 mg / kg and 10.2 mg citric acid / kg. Essential oil yield of gelugur acid of0.3529% b/b, with the physicochemical properties of the specific gravity of 0.9244 b/v,1.4929 refractive index, solubility in 90% alcohol, clear in 1:1 (1 part oil: 1 parts ofalcohol); acid number of 3.8148 and ester numbers of 10.098.